Penerapan metode Tutor Sebaya guna meningkatkan Pemahaman Siswa Kelas XII IPS MAN 1 Kota Mojokerto Tahun Pelajaran 2014/2015 tentang Konsep Integral Tak Tentu pada Mata Pelajaran Matematika - Masruroh, Hanik (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2016)
The perspective that learning mathematics is difficult and requires great effort is common, and understanding in data is that it demands more attention than other subjects. Like reading, mathematics involves basic skills, fluency, and problem solving. Some students experience difficulties especially with computing skills, such as adding, subtracting, and multiplying. Because mathematics learning is associated with failures for so many children, the objectives of this study are: 1) Describe teacher activities in the Application of peer tutoring methods To Increase Understanding of Students of XII IPS MAN 1 Mojokerto City 2014/2015 Academic Year About the Integral Concept of Uncertain Mathematics Subjects. 2) Describe the activities of students in learning activities Application of peer tutoring methods To Increase Understanding of Students of Class XII IPS MAN 1 City of Mojokerto 2014/2015 Academic Year About the Concept of Integration of Uncertainty in Mathematics Subjects.3) Describe learning with peer tutoring methods in improving understanding of Mathematics The Concept of Integral Not Sure in Class XII IPS MAN 1 City of Mojokerto. This research is a classroom action research conducted collaboratively. Designing problem situations, and ways to collaborate with children, is the main focus of meetings that occur between teachers and researchers. This research was conducted at MAN 1 in Mojokerto City. The subjects of this study were 45 Grade XII IPS students. The study was conducted in the odd semester of the 2014/2015 academic year, for 3 months (July, August, September 2014). Procedures for cyclical action research are: 1) planning, 2) implementation, 3) observation, and 4) reflection, through a series of cycles. Data collection through observation (observing), artifacts and documents (testing) and nonstandard tests. Test instrument items with validity test, reliability test, calibration test (level of difficulty) and distinguishing test. the whole process of data analysis is interactive using the Miles and Huberman models with the final mix method analysis. The results of the study concluded: 1) The teacher's activity experienced an increase in Pre-Action obtaining 62.86 percent and increasing in Cycle I by 75 percent and increasing in Cycle II by 87.86 percent. 2) Student activity has increased in Pre-Action to get 42.86 percent and increase in Cycle I by 65 percent and increase in Cycle II by 86.43 percent. 3) The average value of the test (Classical Absorption) has increased in Pre-Action to obtain a result of 65.57 percent and increase in Cycle I by 72.28 percent and increase in Cycle II by 88.28 percent. Classical Learning Completion has increased in Pre-action gets 20 percent and increases in Cycle I by 48.57 percent and increases in Cycle II by 82.86 percent.